Can't stand the look in the mirror? Self-awareness avoidance in borderline personality disorder. Issue 1 (December 2015) - Winter, Dorina; Koplin, Katrin; Lis, Stefanie
Abstract Background Patients with Borderline Personality Disorder (BPD) expect and perceive social rejection stronger than healthy individuals. Shifting ones attention from oneself to others has been suggested as a mechanism to deal with the experience of social rejection. Here, we investigated whether BPD participants avoid increased self-awareness and whether this is done intentionally. Methods Thirty BPD patients and 30 healthy control participants, all naïve of the study's purpose, were asked to choose either a seat facing a mirror (self-awareness) or not facing the mirror (avoidance of self-awareness). Afterwards they were asked to indicate if they have chosen the seat intentionally. Results BPD patients avoided as a trend the chair facing the mirror more often than healthy control participants. 90 % of the patients reported that they made their seating decision intentionally in contrast to 26.7 % of the healthy participants (odd ratio = 24.75). Conclusions Results revealed altered reactions to self-awareness cues in BPD. While BPD patients avoided such a cue slightly more often, they were more often aware of their behavior than healthy participants. As possible explanations, a negative body related, shame-prone self-concept as well as a simultaneously increased degree of self-focused attention are suggested.